Application of Islamic Accounting Profit-Sharing System in Mudharabah Savings Program Based on Fairness - Arief, Arief rahman; Fitriyah, Lailatul; Syafii; Ajeng Fauziah, Dien (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2024)
This study examines the application of the Islamic accounting profit-sharing system in mudharabah savings programs, focusing on how fairness is ensured between depositors and financial institutions. Islamic finance operates on principles of justice, equity, and transparency, emphasizing profit-and-loss sharing instead of guaranteed returns. Using a qualitative case study approach, data were collected through interviews with bank managers, surveys of depositors, and analysis of financial disclosures from Islamic banks. Findings indicate that a predetermined profit-sharing ratio upholds fairness by setting clear expectations for both parties, while transparency in financial reporting enhances depositor trust. However, depositor perceptions of fairness are influenced by the clarity and accessibility of financial disclosures, underscoring the need for simplified reporting and educational support to improve understanding of mudharabah profit-sharing mechanisms. Practical implications include recommendations for Islamic banks to improve transparency, adopt standardized reporting practices, and establish educational initiatives. Limitations include a regional focus and reliance on qualitative data, with future research suggested to broaden the sample, utilize a mixed-methods approach, and explore comparative analyses with other Islamic finance products. This study contributes to the understanding of fairness in Islamic profit-sharing and provides actionable insights to strengthen depositor confidence in mudharabah savings programs